Treating 3 million 2005 : making it happen : the WTO strategy (WHO GenevaCH, 2003)
Provides details of the 'treat 3 million by 2005' initiative. Looks at the strategic framework and changes at WHO. Highlights ways of working with partners and looks beyond 2005.
The WHO and UNAIDS global initiative to provide antiretroviral therapy to 3 million people with HIV/AIDS in developing countries by the end of 2005